1978
DOI: 10.1113/jphysiol.1978.sp012191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repetitive activation on the afterhyperpolarization in dorsal spinocerebellar tract neurones.

Abstract: 1. The changes in the afterhyperpolarization (a.h.p.) with repetitive activation have been studied in dorsal spinocerebellar tract cells of the cat using intracellular recording techniques. 2. The a.h.p. following a single spike was conditioned at different interspike intervals by a single preceding spike. In the majority of neurones the a.h.p. following a spike added approximately linearly with that generated by a preceding spike. 3. In other cells the a.h.p. following a spike was instead depressed by a prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…In two preceding papers the a.h.p. properties of DSCT neurones were described Gustafsson & Zangger, 1978). In order to evaluate the role of the a.h.p.…”
Section: A Dsct Model Neuronementioning
confidence: 99%
See 3 more Smart Citations
“…In two preceding papers the a.h.p. properties of DSCT neurones were described Gustafsson & Zangger, 1978). In order to evaluate the role of the a.h.p.…”
Section: A Dsct Model Neuronementioning
confidence: 99%
“…conductance evoked by each spike is unaffected by the succeeding spikes; i.e. there is a linear superposition of successive a.h.p.s (Gustafsson & Zangger, 1978).…”
Section: A Dsct Model Neuronementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, motoneurones with accelerating firing patterns showed a decrease in the AHP amplitude during successive spikes. Gustafsson & Zangger (1978) have shown that, in cat dorsal spinocerebellar tract neurones, changes in firing pattern could be explained by the presence of AHP summation or depression. Previously (Viana et al 1993b), we have demonstrated that the AHP conductance in HMs is due to activation of an apamin-sensitive calcium-activated K+ conductance (Barrett & Barrett, 1976).…”
Section: Changes In Current Thresholdmentioning
confidence: 99%